Genome-wide analysis of clopidogrel active metabolite levels identifies novel variants that influence antiplatelet response. Issue 4 (April 2017) - Backman, Joshua D.; O'Connell, Jeffrey R.; Tanner, Keith; Peer, Cody J.; Figg, William D.; Spencer, Shawn D.; Mitchell, Braxton D.; Shuldiner, Alan R.; Yerges-Armstrong, Laura M.; Horenstein, Richard B.; Lewis, Joshua P.
Abstract : Clopidogrel is one of the most commonly used therapeutics for the secondary prevention of cardiovascular events in patients with acute coronary syndromes. However, considerable interindividual variation in clopidogrel response has been documented, resulting in suboptimal therapy and an increased risk of recurrent events for some patients. In this investigation, we carried out the first genome-wide association study of circulating clopidogrel active metabolite levels in 513 healthy participants to directly measure clopidogrel pharmacokinetics. We observed that the CYP2C19 locus was the strongest genetic determinant of active metabolite formation ( P =9.5×10 –15 ). In addition, we identified novel genome-wide significant variants on chromosomes 3p25 (rs187941554, P =3.3×10 –11 ) and 17q11 (rs80343429, P =1.3×10 –8 ), as well as six additional loci that showed suggestive evidence of association ( P ⩽1.0×10 –6 ). Four of these loci showed nominal associations with on-clopidogrel ADP-stimulated platelet aggregation ( P ⩽0.05). Evaluation of clopidogrel active metabolite concentration may help identify novel genetic determinants of clopidogrel response, which has implications for the development of novel therapeutics and improved antiplatelet treatment for at-risk patients in the future. Abstract : Supplemental Digital Content is available in the text.